2010
DOI: 10.1007/s12603-010-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

The status of vitamins B6, B12, folate, and of homocysteine in geriatric home residents receiving laxatives or dietary fiber

Abstract: Oat-bran helps to improve constipation management and B12 bioavailability in elderly, with multiple chronic diseases who live in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…No symptoms and signs are specific for B6 deficiency. In this study, as in other reports, malnutrition, inactivity, old age, low s-albumin and s-ALAT values, and high homocysteine values were associated with B6 deficiency and seem reasonable to have in mind [8,15,17,28,29]. …”
Section: Discussionsupporting
confidence: 87%
“…No symptoms and signs are specific for B6 deficiency. In this study, as in other reports, malnutrition, inactivity, old age, low s-albumin and s-ALAT values, and high homocysteine values were associated with B6 deficiency and seem reasonable to have in mind [8,15,17,28,29]. …”
Section: Discussionsupporting
confidence: 87%
“…Commonly this is treated with laxatives but ideally the consumption of whole grains, legumes, fruits and vegetables should be increased (Slavin 2008). Tailored products, such as pea hull fibre added to usual foods (Dahl et al 2003) and oat bran (Sturtzel et al 2010), have been shown to be helpful in improving constipation management, and oat bran was also reported to improve vitamin B12 bioavailability.…”
Section: Physiology Nutrition and Lifestyle Of The Elderlymentioning
confidence: 99%
“…Oat bran can reduce serum cholesterol due to it capacity to bind bile acid (Drizikova, Dongowski, Gebhardt, & Habel, 2005). Oat bran may also improve constipation management and B12 bioavailability in the elderly with multiple chronic diseases (Sturtzel, Dietrich, Wagner, Gisinger, & Elmadfa, 2010). Consumption of citrus peel was associated with significant reduction of both serum total and HDL-cholesterol levels (Wisker, Daniel, & Feldheim, 1994).…”
Section: Introductionmentioning
confidence: 99%